An assessment of the general public's knowledge of fatal fetal anomalies. (31st August 2018) - Power, Stacey; Meaney, Sarah; O'Donoghue, Keelin
Abstract: Objective: The objective of the study is to evaluate the general population's knowledge of fatal fetal anomaly (FFA). Methods: Descriptive statistics were utilised to describe the data. Chi‐square tests assessed associations with knowledge of FFA, termination of pregnancy (TOP) for FFA, and perinatal palliative care (PPC). Results: Nine hundred seventy adults of the Irish population selected by random digit dialling with 83.9% (n = 814) agreed to partake. Only 30% could correctly define FFA with little knowledge demonstrated regarding the classification of FFA. Almost half of the respondents were unaware that medical intervention was required for survival once born. Half of respondents stated that they did not know if PPC could commence at diagnosis, once the baby reached 24 weeks or not until the baby was born alive. One in 5 had knowledge that medical follow‐up after TOP for FFA was available, and a third were unaware that bereavement care was available following a TOP for FFA. Conclusion: This study identifies lack of accurate knowledge on FFA, its classification, diagnosis, survival, and supports available following a diagnosis of FFA among the general public. This knowledge deficit highlights the need for improved health information about FFA in antenatal education and public health campaigns to facilitate informed decision‐making following a FFA diagnosis. Abstract : What's already known about this topic? Improvements in antenatal screening have increased the number of foetal anomalies being diagnosed during pregnancy. A fatal foetal anomaly (FFA) diagnosis and the subsequent discussion on termination (TOP) for FFA and perinatal palliative care (PPC) are associated with emotional distress and grief. What does this study add? Identifies knowledge inaccuracies among the general public regarding FFA, PPC, and supports available for TOP for FFA. Recognises the need for health education within maternity services regarding FFA.